Pelatihan Nearpod bagi Guru untuk Meningkatkan Interaktivitas Pembelajaran di SD Negeri 1 Toyareka - Mustofa, Dinar; Darmayanti, Irma; Pramono, Agus; Apitiadi, Satyo Dwi; Kusuma, Velizha Sandy; Saputra, Dhanar Intan Surya (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
The lack of skills among teachers at SD Negeri 1 Toyareka in utilizing interactive learning technology has become a challenge affecting the effectiveness of classroom teaching. This issue prompted a community service initiative in the form of training on the use of the Nearpod platform to enhance teacher’s digital competencies. The objective of this activity was to provide teachers with practical knowledge and skills in using Nearpod to create more interactive learning experiences. The training was conducted in several stages, starting with a needs analysis to assess infrastructure readiness and identify technical challenges, followed by a two-day training session covering an introduction to Nearpod features, hands-on material development exercises, and classroom simulation applications. Evaluation was conducted to measure participants’ improvement in understanding and skills. The training results indicated that most teachers successfully mastered the basic features of Nearpod, such as creating and delivering interactive learning materials. Additionally, teachers reported increased confidence in integrating this technology into their teaching practices. Technical issues, such as unstable internet connections, were the main challenges encountered during the training. Overall, this training had a positive impact on improving teacher’s competencies in integrating learning technology, which has the potential to enrich students learning experiences and enhance classroom interactivity.ABSTRAKKurangnya keterampilan guru SD Negeri 1 Toyareka dalam memanfaatkan teknologi pembelajaran interaktif menjadi tantangan yang memengaruhi efektivitas pembelajaran di kelas. Hal ini mendorong dilakukannya kegiatan pengabdian masyarakat berupa pelatihan penggunaan platform Nearpod untuk meningkatkan kompetensi digital guru. Tujuan kegiatan ini adalah memberikan pemahaman dan keterampilan praktis bagi guru dalam menggunakan Nearpod guna menciptakan pembelajaran yang lebih interaktif. Pelatihan dilaksanakan melalui beberapa tahapan, yaitu analisis kebutuhan untuk menilai kesiapan infrastruktur dan identifikasi kendala teknis, diikuti oleh pelatihan selama dua hari yang mencakup pengenalan fitur Nearpod, latihan pembuatan materi ajar, serta simulasi penerapan di kelas. Evaluasi dilakukan untuk mengukur peningkatan pemahaman dan keterampilan peserta. Hasil pelatihan menunjukkan bahwa sebagian besar guru berhasil menguasai fitur dasar Nearpod, seperti membuat dan menyajikan materi pembelajaran interaktif. Selain itu, para guru merasa lebih percaya diri dalam menggunakan teknologi ini di kelas. Kendala teknis, seperti koneksi internet yang tidak stabil, menjadi tantangan utama yang dihadapi selama pelaksanaan. Secara keseluruhan, pelatihan ini memberikan dampak positif terhadap peningkatan kompetensi guru dalam mengintegrasikan teknologi pembelajaran, yang berpotensi memperkaya pengalaman belajar siswa dan meningkatkan interaktivitas di kelas.